Mechanical fault detection method of weighing device sensor faced on internet of things. (2nd December 2021) - Dong, Yan; Bi, Shiying
The load cell is an indispensable control device in the weighing process, but there is currently no method for mechanical fault diagnosis of the load cell. This article aims to explore an effective method that can quickly detect the mechanical failure of the load cell through simulation experiments. In this paper, the zero point output signal of the load cell is first sampled and set to n, and the standard deviation of the value of n is found by using the continuous value of the sliding window, and finally the ratio of the standard deviation to the normal output standard deviation is taken as the test basis. The experimental results show that the method can monitor the operating status of multiple devices in real time and predict equipment failure time, and can effectively maintain the normal operation of mechanical equipment.